Prediction of Stature in Males of Tamil Population from Measurements of Percutaneous Tibial Length (Medico Legal Update, 2021)
Forensic experts are often in confrontation with the challenging task of determination of stature along withrace, age etc. for the purpose of establishing the identity of the deceased individual in those circumstanceswhere only skeletal remains, mutilated or dismembered body parts, extremely decomposed body parts etc.are provided by investigating authorities. In the current study, a genuine attempt has been made to arriveat the population specific regression equation for stature prediction from the percutaneous length of Tibia.The subjects chosen for this study include 120 adult males belonging to Tamil population falling withinthe age range of 21 to 30 years. Stature and percutaneous lengths of right and left Tibia from each subjectwere precisely recorded following standard protocols using appropriate instruments and analysis of thedata collected was done applying Pearson correlation through SPSS software version 26 to arrive at theregression equations for stature assessment based on percutaneous right and left Tibial lengths respectively.By comparing the regression formulae obtained from the present study with those derived from variouspopulation specific studies done on Indian population, our regression equations found to be distinctive toTamil population and therefore can be authentically applied for calculation of stature of deceased frompercutaneous Tibial length in males of Tamil population whenever skeletal remains are available.